2021
DOI: 10.1016/j.ejogrb.2021.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Popularity of endocrine endometriosis drugs and limited alternatives in the present and foreseeable future: A survey among 1420 affected women

Abstract: Objectives: Endocrine drugs represent an important cornerstone of endometriosis therapy. Pharmaceutical alternatives with similar efficacy remain out of sight in the near future. Aim of this study is to investigate attitudes and perceptions concerning endocrine therapies among affected women. Study design: An online survey was distributed via social media in Austria, Germany, and Switzerland. Primary endpoints were satisfaction, attitudes and perceptions towards endocrine endometriosis drugs and secondary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…While hormonal drugs are the mainstay of current therapeutics, a recent survey of 1420 patients with endometriosis in Austria, Germany, and Switzerland found that an overwhelming proportion of them hold a negative attitude toward hormonal drugs, and the majority of them disliked the side effects of these drugs, especially amongst young, city-dwelling, educated women (Burla et al 2021). Remarkably, 95.3% of the surveyees expressed preference for plant-based products, preferably in oral form (Burla et al 2021). This demand contrasts sharply with resounding failure in clinical trials on non-hormonal drugs in endometriosis and adenomyosis (Guo & Evers 2013, Guo 2014) and highlights the medical need that has not been fulfilled.…”
Section: Development Of Novel Therapeuticsmentioning
confidence: 99%
“…While hormonal drugs are the mainstay of current therapeutics, a recent survey of 1420 patients with endometriosis in Austria, Germany, and Switzerland found that an overwhelming proportion of them hold a negative attitude toward hormonal drugs, and the majority of them disliked the side effects of these drugs, especially amongst young, city-dwelling, educated women (Burla et al 2021). Remarkably, 95.3% of the surveyees expressed preference for plant-based products, preferably in oral form (Burla et al 2021). This demand contrasts sharply with resounding failure in clinical trials on non-hormonal drugs in endometriosis and adenomyosis (Guo & Evers 2013, Guo 2014) and highlights the medical need that has not been fulfilled.…”
Section: Development Of Novel Therapeuticsmentioning
confidence: 99%
“…Even though there is an abundance of endometriosis-related information online, filtering and assessing the quality of information can be challenging, as people make little use of source credibility [ 13 ]. Available information on endometriosis is often of low quality, inaccurate, or skewed toward the diagnosis or it conveys negative connotations, while high-quality information is challenging for a lay audience to comprehend [ 14 , 15 ]. These circumstances can induce feelings of fear and helplessness [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the development of non-hormonal drugs for endometriosis so far has been painfully stagnant [ 9 , 10 ], and the resultant disappointment is palpable [ 11 ]. Remarkably, a recent study reports that nearly 90% of patients with endometriosis are not satisfied with hormonal drugs, and over 95% of patients would have preferred plant-based products [ 12 ]. This study provides a strong impetus to search for novel non-hormonal drugs for endometriosis.…”
Section: Introductionmentioning
confidence: 99%